Dysregulated MicroRNA Fingerprints and Methylation Patterns in Hepatocellular Carcinoma, Cancer Stem Cells, and Mesenchymal Stem Cells - Nasr, Mohamed A.; Salah, Radwa Ayman; Abd Elkodous, M.; Elshenawy, Shimaa E.; El-Badri, Nagwa (Frontiers in Cell and Developmental Biology, 2019)
Hepatocellular carcinoma (HCC) is one of the top causes of cancer mortality worldwide. Although HCC has been researched extensively, there is still a need for novel and effective therapeutic interventions. There is substantial evidence that initiation of carcinogenesis in liver cirrhosis, a leading cause of HCC, is mediated by cancer stem cells (CSCs). CSCs were also shown to be responsible for relapse and chemoresistance in several cancers, including HCC. MicroRNAs (miRNAs) constitute important epigenetic markers that regulate carcinogenesis by acting post-transcriptionally on mRNAs, contributing to the progression of HCC. We have previously shown that co-culture of cancer cells with mesenchymal stem cells (MSCs) could induce the reprogramming of MSCs into CSC-like cells. In this review, we evaluate the available data concerning the genetic and epigenetic regulation of miRNAs through methylation and the possible role of this regulation in stem cell and somatic reprogramming in HCC.